Evaluation of Death Cases Suspected of in Toxication for Legal and Medical Documents - Müsellim, Nurşen Turan; Üzün, İbrahim; Gürpınar, Süleyman Serhat (The Bulletin of Legal Medicine, 2002)
Among intoxication cases, factors like age and sex of intoxicated people, substance speciality, whether more than one substance is used, therapy, complications are studied in Turkey and other countries. At the 5th Specialization Board of the State Institute of the Forensic Medicine of Turkey, when the cases related to intoxication are evaluated and concluded, some deficiencies about evidences effect last decision about intoxication. We intended to study the importance of statistical meaning of all variables effecting the conclusion statistically. Reports of the 5th Specialization Board of the State Institute of the Forensic Medicine of Turkey, about intoxicated cases or suspected intoxicated cases at the year of 2001 are examined. In all these documents, age, sex, drug/ substance method of duration between substance intake and investigation of substance in laboratuary, whether any complications and any disease exist among intoxicated people, any reason other than intoxication is present to cause death of people, whether any treatment is used for intoxicated people, number of substances that are used, whether medical and legal document is present, are investigated. All data are statistically examined and effect of all variables to last decision is discussed.Key words: Intoxication, postmortem, autopsy, forensic medicine.
Keywords: intoxication; postmortem; autopsy; forensic medicine